Model of action plan for management systems energy - Ortiz Garcıa, Jose Dagoberto; Leon Velasquez, Elizabeth; Ramırez Valencia, Eduardo (Visión electrónica, 2014)
The ISO 50001 standard unified in 2011, internationally, the accumulated knowledge concerning integrated management systems of energy; ie learning, dissemination, and implementation requirements are in force, particularly in routine activities of the business sector. Therefore, this article presents the general ideas about the most important features to consider in the developing of action plans, adaptable to business peculiarities: actions, objectives of each action, description, times when you must run, the estimated budget, both human and financial resources available and technical and human resources responsible for the success of the plan. Is proposed as research product, a new tool based on the ISO 50001 standard and the “ Guide to implementation of a comprehensive energy management” developed by the Unit of Mining and Energy Planning (UPME).